2016
DOI: 10.1016/j.jinf.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Viral load is strongly associated with length of stay in adults hospitalised with viral acute respiratory illness

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 32 publications
1
29
0
1
Order By: Relevance
“…A growing body of evidence shows a correlation of respiratory viral load and patient outcome. In one study of immunocompetent adult patients, age and hospitalization time were associated with earlier reverse transcriptase PCR (RT-PCR) cycle threshold (C T ) values for FLUA/B of Յ20 than later C T values (242). Association of viral load and outcome can also vary by genotype, as RV-A viral loads were higher in patients with severe disease than in patients without severe disease, while no difference in viral load was observed for patient groups infected with RV-C (243).…”
Section: Understanding Applications Of Molecular Detection Approachesmentioning
confidence: 99%
“…A growing body of evidence shows a correlation of respiratory viral load and patient outcome. In one study of immunocompetent adult patients, age and hospitalization time were associated with earlier reverse transcriptase PCR (RT-PCR) cycle threshold (C T ) values for FLUA/B of Յ20 than later C T values (242). Association of viral load and outcome can also vary by genotype, as RV-A viral loads were higher in patients with severe disease than in patients without severe disease, while no difference in viral load was observed for patient groups infected with RV-C (243).…”
Section: Understanding Applications Of Molecular Detection Approachesmentioning
confidence: 99%
“…Previous studies have hypothesized that viral load of some respiratory viruses correlate with disease severity [2], but this association is not clear in the case of influenza virus infection [3,4]. On the contrary, other authors have found that high influenza viral load is associated with a longer duration of hospital stay in adults with viral acute respiratory illness [5]. On this basis, we decided to analyze the role of influenza viral load in the outcome of the patients included in the same cohort of our previous paper [1].…”
Section: Introductionmentioning
confidence: 96%
“…Other endpoints can include patient reported outcomes, such as the FluiiQ™ questionnaire (Osborne et al, 2011), or the Flu-Pro © survey (Powers et al, 2016). Virological endpoints have shown good correlation with clinical measures (Carrat et al, 2008) and virus load at admission has been shown to correlate with the length of hospital stay (Clark et al, 2016). Virus load may thus minimize the issues around the heterogeneity of the population.…”
Section: What Endpoints Make Sense In Clinical Trials Of Severe Influmentioning
confidence: 99%